Influence of habituation on pseudo-haptic weight perception of virtual objects - Ito, Kenta; Ban, Yuki; Warisawa, Shin’ichi (Frontiers in Virtual Reality, 2024)
As the demand for realistic sensations in virtual reality (VR) environments escalates, interfaces that exploit cross-modal interactions between vision and haptics are gaining prominence. Pseudohaptics, offering a tactile illusion without mechanical feedback devices, has emerged as a viable solution to enhance user immersion by simulating various sensations such as texture, fluid resistance, and weight. However, a potential issue in the long-term effectiveness of these illusions, particularly habituation, where the illusion diminishes after prolonged exposure, remains a concern. This study investigates whether habituation to pseudo-haptic weight illusions occurs with extended use. We conducted quantitative measurements of pseudo-haptic weight perception before and after prolonged exposure. The findings indicate a diminishing effect of pseudo-haptic weight illusion with repeated exposure, particularly among participants with high accuracy in weight perception. This study contributes important insights into the design of VR experiences, highlighting the need to consider the habituation effects when implementing pseudo-haptic illusions for weight perception.